Publisher Correction: Precisely printable and biocompatible silk fibroin bioink for digital light processing 3D printing - Soon Hee Kim (Nature Portfolio, 2018)
The original version of this Article contained errors in Figs. 5 and 6. In Fig. 5b, the second panel on the bottom row was stretched out of proportion. In Fig. 6d, the first panel was also stretched out of proportion. In Fig. 6f, the fifth panel inadvertently repeated the fourth. This has been corrected in both the PDF and HTML versions of the Article.